Structural Insights into α-Synuclein Fibril Polymorphism: Effects of Parkinson's Disease-Related C-Terminal Truncations. Issue 19 (6th September 2019) - Ni, Xiaodan; McGlinchey, Ryan P.; Jiang, Jiansen; Lee, Jennifer C.
Abstract: Lewy bodies, hallmarks of Parkinson's disease, contain C-terminally truncated (ΔC) α-synuclein (α-syn). Here, we report fibril structures of three N-terminally acetylated (Ac) α-syn constructs, Ac1–140, Ac1–122, and Ac1–103, solved by cryoelectron microscopy. Both ΔC-α-syn variants exhibited faster aggregation kinetics, and Ac1–103 fibrils efficiently seeded the full-length protein, highlighting their importance in pathogenesis. Interestingly, fibril helical twists increased upon the removal of C-terminal residues and can be propagated through cross-seeding. Compared to that of Ac1–140, increased electron densities were seen in the N-terminus of Ac1–103, whereas the C-terminus of Ac1–122 appeared more structured. In accord, the respective termini of ΔC-α-syn exhibited increased protease resistance. Despite similar amyloid core residues, distinctive features were seen for both Ac1–122 and Ac1–103. Particularly, Ac1–103 has the tightest packed core with an additional turn, likely attributable to conformational changes in the N-terminal region. These molecular differences offer insights into the effect of C-terminal truncations on α-syn fibril polymorphism. Graphical Abstract: Unlabelled Image Highlights: Effects of C-terminal truncations on α-syn fibril formation were studied. Fibril helical twists increased upon the removal of C-terminal residues. Fibril structures of full length and ΔC-α-syn were solved by cryoEM. Conformational differences were revealed at N- and C-termini. Structural insights were gained on α-syn fibril polymorphism.